The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.19163/2307-9266-2019-7-5-291-299
|View full text |Cite
|
Sign up to set email alerts
|

Correction of psychological and neurological signs of alcohol hangover in rats with acetylcysteine

Abstract: Федеральное государственное бюджетное образовательное учреждение высшего образования «Волгоградский государственный медицинский университет» Министерства здравоохранения Российской Федерации 400131, Россия, г. Волгоград, площадь Павших Борцов, д. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In the framework of the present work, it was found that in the rats that had received NAC before acute ethanol intoxication a decrease in glutathione level in hepatocytes was less pronounced than in the rats that had not received NAC on the background of ethanol intoxication. This is consistent with the results of our previous studies (Kupchik et al 2012, Kurkin et al 2019, Morkovin et al 2019a, in which the therapeutic effects of NAC were evaluated (with a single oral administration after alcohol intoxication). In both cases, the animals were injected intraperitoneally with ethanol, which excluded the pharmacokinetic interaction of NAC with ethanol, which could have contributed to a lower systemic absorption of the latter.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the framework of the present work, it was found that in the rats that had received NAC before acute ethanol intoxication a decrease in glutathione level in hepatocytes was less pronounced than in the rats that had not received NAC on the background of ethanol intoxication. This is consistent with the results of our previous studies (Kupchik et al 2012, Kurkin et al 2019, Morkovin et al 2019a, in which the therapeutic effects of NAC were evaluated (with a single oral administration after alcohol intoxication). In both cases, the animals were injected intraperitoneally with ethanol, which excluded the pharmacokinetic interaction of NAC with ethanol, which could have contributed to a lower systemic absorption of the latter.…”
Section: Resultssupporting
confidence: 92%
“…The prevalence of alcoholism is one of the central public health problems in medical, social and economic terms. According to the latest WHO data, alcoholism is one of the leading causes of health deterioration worldwide, and the European Region has the highest premature mortality attributed to ethanol consumption (due to an increase in the number of somatic pathologies and death due to alcohol intoxication) (Kupchik et al 2012, Kurkin et al 2019, Morkovin et al 2019a.…”
Section: Resultsmentioning
confidence: 99%